IMD World Competitiveness Rankings - Rory Mulholland; Dermot P. Coates (National Competitiveness and Productivity Council (NCPC), 2024)
Ireland is ranked 4th out of 67 economies in the IMD's World Competitiveness Yearbook 2024, dropping two places from last year. Amongst the euro area countries, Ireland continues to rank as the most competitive. The marginal decline in Ireland's ranking largely reflects a decline under the Economic Performance pillar where Ireland has dropped from 1st place in 2023 to 10th in 2024 - this was driven by slowing GDP growth last year. Ireland's Government Efficiency ranking has also disimproved - ranked 6th (down from 3rd in 2023). Ireland has maintained its ranking in terms of Business Efficiency and has improved its Infrastructure ranking to 17th (up from 19th in 2023).
Keywords: 330